A comparative assessment on Common Rail Direct Injection (CRDI) engine characteristics using low viscous biofuel blends. (25th December 2018) - Ashok, B.; Nanthagopal, K.; Chaturvedi, Bhaskar; Sharma, Shivam; Thundil Karuppa Raj, R.
Highlights: Lemon and Orange Peel Oil is extracted by steam distillation from waste peels. B20 blends were prepared and fueled in CRDI engine by varying injection parameters and EGR. Orange peel oil exhibits better performance over lemon peel oil and diesel fuel. Benefits in HC, CO and Smoke emissions due to the biofuel blends were noticed. Abstract: The current study compares the performance, emission and combustion characteristics of two different biofuel extracted from waste peels of lemon and orange fruit through steam distillation process in common rail direct injection engine. The study is further extended by variation of parameters such as injection pressures, split injection quantities and exhaust gas recirculation. The brake thermal efficiency for orange peel is higher than diesel and lemon peel oil at 600 bar with 10% of pilot fuel quantity. The similar cetane index of orange peel oil (OPO) means there is minimal performance drop for its blend and lemon peel oil (LPO) performs well as compared to diesel however this benefit is not greater than OPO. However, for 30% pilot fuel quantity the fuel efficiency is dropped by 10.74% and 4.72% for OPO and LPO respectively as compared to 10% pilot fuel quantity. Through the use of a greater quantity of pilot fuel injection, the low viscosity of LPO further increases its performance characteristics whereas OPO sees a decrement. The inherent oxygen content of both biofuel blends shows reduced emission of un-burnt hydrocarbon and carbon monoxide emissions under 600 bar and 10% pilot injection with the penalty of oxides of nitrogen emission.